2017
DOI: 10.1007/s12028-017-0440-5
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Brief Versus Extended Seizure Prophylaxis After Aneurysmal Subarachnoid Hemorrhage

Abstract: This study was underpowered to demonstrate superiority of extended LEV for seizure prophylaxis, although a trend to benefit was seen. Seizures primarily occurred in those with radiographic EBI, suggesting targeted prophylaxis may be preferable. Larger trials are required to evaluate optimal chemoprophylaxis in SAH, especially in light of worse outcomes in those receiving extended treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Increasing interest in using levetiracetam for seizure prophylaxis after TBI and SAH, as well as treatment of status epilepticus, has led to extensive use of levetiracetam in patients with ARC. [60][61][62] Levetiracetam undergoes partial hydrolysis in the serum, with nearly all of the hydrolyzed fraction and the remaining unchanged fraction (~70-80% of the dose) eliminated renally. Levetiracetam clearance correlated modestly well with estimated Cl cr in a neurocritical care cohort (r 2 = 0.527, p=0.01).…”
Section: Dosing Considerationsmentioning
confidence: 99%
“…Increasing interest in using levetiracetam for seizure prophylaxis after TBI and SAH, as well as treatment of status epilepticus, has led to extensive use of levetiracetam in patients with ARC. [60][61][62] Levetiracetam undergoes partial hydrolysis in the serum, with nearly all of the hydrolyzed fraction and the remaining unchanged fraction (~70-80% of the dose) eliminated renally. Levetiracetam clearance correlated modestly well with estimated Cl cr in a neurocritical care cohort (r 2 = 0.527, p=0.01).…”
Section: Dosing Considerationsmentioning
confidence: 99%
“…114 A second study in patients with aSAH evaluated open label levetiracetam for seizure prophylaxis for either 3 days or until hospital discharge and showed no difference in the incidence of seizures but worse neurological outcomes in the group that received a prolonged duration of therapy. 115 Additional data on phenytoin in this scenario suggest an association with worsened longterm cognitive outcomes, as well as a drug interaction with nimodipine, making it a less than ideal agent for prophylaxis in this patient population. [116][117][118] Current guidelines suggest that the use of a prophylactic antiseizure drug may be considered in the immediate posthemorrhagic period, but therapy should not exceed 7 days and phenytoin should be avoided.…”
Section: Neurological Injurymentioning
confidence: 97%
“…In a systematic review by Lanzino et al, a 3-day seizure prophylaxis regimen was found to provide sufficient control for post-operative seizures, and they related the worse outcome associated with AEDs to phenytoin (28). Other recent studies also emphasize brief courses of 3 to 7 days of prophylaxis and save the extended prophylaxis for those with mentioned risk factors (14,29). From March 2016, we have switched to a 1-week course of phenytoin or levetiracetam and the results were promising so far for seizure control (13).…”
Section: Future Perspectivementioning
confidence: 99%